Autonomous clock ensemble algorithm for GNSS applications. Issue 2 (23rd June 2020) - Coleman, Michael J.; Beard, Ronald L.
Abstract: The US Naval Research Laboratory (NRL) has developed clock ensembles for a number of vital GNSS projects and services throughout the US and international community. Some efforts include algorithms for local realization of Coordinated Universal Time; participation in the upgrade of the Global Positioning System (GPS) system time; the initial implementation of a coherent geophysical reference time known as IGS Time (IGST); and development of various Department of Defense (DoD) capabilities for the dissemination and transfer of precise time. This paper will cover the major algorithm components that compute and maintain a robust and stable time reference for the most stringent applications mentioned here. These components include automated alert and response to clock anomalies and reduction of measurement weight in response to large clock measurement residuals. Both real and simulated data have been used to validate the ensemble algorithm and its products for reliable and robust usage in these environments.